Photo-responsive polymeric nanocarriers for target-specific and controlled drug delivery. Issue 38 (28th September 2021) - Martín Giménez, Virna M.; Arya, Geeta; Zucchi, Ileana A.; Galante, María J.; Manucha, Walter
Abstract : Conventional drug delivery systems often have several pharmacodynamic and pharmacokinetic limitations related to their low efficacy and bad safety. Abstract : Conventional drug delivery systems often have several pharmacodynamic and pharmacokinetic limitations related to their low efficacy and bad safety. It is because these traditional systems cannot always be selectively addressed to their therapeutic target sites. Currently, target-specific and controlled drug delivery is one of the foremost challenges in the biomedical field. In this context, stimuli-responsive polymeric nanomaterials have been recognized as a topic of intense research. They have gained immense attention in therapeutics – particularly in the drug delivery area – due to the ease of tailorable behavior in response to the surroundings. Light irradiation is of particular interest among externally triggered stimuli because it may be specifically localized in a contact-free manner. Light–human body interactions may sometimes be harmful due to photothermal and photomechanical reactions that lead to cell death by photo-toxicity and/or photosensitization. However, these limitations may also be overcome by the use of photo-responsive polymeric nanostructures. This review summarizes recent developments in photo-responsive polymeric nanocarriers used in the field of drug delivery systems, including nanoparticles, nanogels, micelles, nanofibers, dendrimers, and polymersomes, as well as their classification and mechanisms of drug release.